2022
DOI: 10.1111/nicc.12854
|View full text |Cite
|
Sign up to set email alerts
|

Nursing workload assessment in an intensive care unit: A retrospective observational study using the Nursing Activities Score

Abstract: Background: Nursing Activities Score (NAS) is a promising tool for calculating the nursing workload in intensive care units (ICU). However, data on intensive care nursing activities in Portugal are practically non-existent.Aim: To assess the nursing workload in a Portuguese ICU using the NAS.Study Design: Retrospective cohort study developed throughout the analysis of the electronic health record database from 56 adult patients admitted to a six-bed Portuguese ICU between 1 June-31 August 2020. The nursing wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…However, the data showed that all the study participants needed at least basic care activities related to the care and prevention of pressure ulcers and daily dressing changes, while 26.1% needed frequent dressing changes (at least once per nursing shift) and/or extensive wound care. These data were consistent with other studies developed in intensive care units that highlight the need to preferentially assess the nursing workload that each participant generates [ 39 ] and the specificities of each shift [ 40 , 41 ] instead of calculating nursing ratios according to occupancy rates, average nursing workload per participant, and/or the total 24-h nursing workload in the intensive care unit [ 2 ]. Specifically, regarding the wound treatment, when the wound is complex, more time is needed, as well as more differentiated interventions by different health professionals aiming to choose the best dressing options [ 42 ].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…However, the data showed that all the study participants needed at least basic care activities related to the care and prevention of pressure ulcers and daily dressing changes, while 26.1% needed frequent dressing changes (at least once per nursing shift) and/or extensive wound care. These data were consistent with other studies developed in intensive care units that highlight the need to preferentially assess the nursing workload that each participant generates [ 39 ] and the specificities of each shift [ 40 , 41 ] instead of calculating nursing ratios according to occupancy rates, average nursing workload per participant, and/or the total 24-h nursing workload in the intensive care unit [ 2 ]. Specifically, regarding the wound treatment, when the wound is complex, more time is needed, as well as more differentiated interventions by different health professionals aiming to choose the best dressing options [ 42 ].…”
Section: Discussionsupporting
confidence: 87%
“…Being admitted to a hospital is an important measure of frailty [ 21 ], whereby the patients admitted to intensive care units [ 22 ] are normally associated to higher levels of nursing workload [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, negative workplace environments and unsustainable workloads can have deleterious impacts that compromise patient safety. 13 The challenge of heavy workloads and staff shortages is an important issue, which commonly arises in ICU settings and reflects a disquieting dichotomy between workload requirements versus expectations and workforce availability versus capability. Further to this it represents a very challenging situation when essential care is required, but the potential for further harm because of scarce human resources exists.…”
Section: Workplace Environmentmentioning
confidence: 99%